Mengapa Wanita Tidak Memilih Bersalin Di Rumah Sakit? - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Pre-natal interventions have been widely implemented as the main strategy to reduce maternal mortality and morbidity. This strategy, however, is not sufficient to attack the problem due to inparticular, inappropriate referral system and untimely intervention. Recognition of these problems combined with a relatively high proportion of unknown cause of maternal death has led to different priorities in Safe Motherhood Initiative, among those are to improve access to emergency obstetric care. This consequently means to remove any obstacles in the utilization of such services. This study aims to identify service factors which perceived by the user to influence household decision making in the utilisation of district hospital delivery facilities. A qualitative study using an indepth interview was performed in Klaten district hospital to collect information regarding reasons for choosing a particular facility to give birth. interviews of 23 women who had experienced at least two deliveries revealed 2 categories of barriers. Service delivery, namely regulations for visitors, negative staff attitude, and care for the newborn, was expressed as a substantial barrier for women to give birth at the hospital. Surprisingly, distance and cost appeared not to be the main obstacle. These findings imply that service factors may have a significant influence in the decision to use a hospital maternity service on the subsequent pregnancy. The relatively less importance of distance and cost in relation to utilisation may suggest further hypothesis, that is if cultural factors are to be incorporated into the provision of a modern maternity service, women may be more capable to overcome problems associated with distance and cost.